Zredukuj wyrazy podobne, a następnie oblicz wartość wyrażenia
a) 19x - 16 + 7y - 27 x -5 y dla x = 2, y = - 4
b) 4x - 13y - 11 x + 7 + 7,5 y - 5x - 2 dla x = 2, y = - 4


Odpowiedź :

a)19x-27x+7y-5y-16= -8x+2y-16= -16-8-16= -40

b)4x-11x--5x-13y+7,5y+7-2= -12x -5,5y+5= -24+22+5=3

Odpowiedź:

A) dla x=2

19*2-16+7y-27*2-5y=0

22+2y-54=0

2y=32

y=16

Dla y= - 4

19x-16+7*(-4)-27x-5*(-4)=0

10x-44+20=0

10x=24

x=2,4

B)dla x=2

4*2-13y-11*2+7+7,5y-5*2=0

8-5,5y-15-12=0

-5,5y=19

y=3,45

Dla y= -4

4x-13*(-4)-11x+7+7,5y*(-4)-5x-2=0

-12x+59-30-2=0

-12x=27

x=2,25

Mam nadzieję że jest dobrze :)

Szczegółowe wyjaśnienie: